Confirmatory Factors Analysis of Multicultural Leadership of Youth in the Three Southern Border Provinces of Thailand - Kasetchai Laeheem; Punya Tepsing; Khaled Hayisa-e (Societies, 2025)
Developing multicultural leadership in youth is crucial for fostering social harmony, emphasizing cross-cultural communication, adaptability, creative problem solving, and ethical leadership, particularly in Thailand’s three southern border provinces. This study aimed to analyze the confirmatory factors and assess the validity of the measurement model for multicultural leadership among youth in Thailand’s three southern border provinces. The study sample comprised 640 participants, and the data were analyzed using second-order confirmatory factor analysis. The findings revealed that multicultural leadership among youth in the region consists of the following six key components: (1) awareness and acceptance of cultural diversity, (2) intercultural communication skills, (3) flexibility and adaptability in multicultural contexts, (4) creative problem solving in a multicultural context, (5) building intercultural collaboration networks, and (6) developing culturally relevant morality and ethics. The measurement model demonstrated a good fit with the empirical data. Considering the Chi-square value of 411.81, p-value of 0.07, the relative Chi-square (χ2/df) was 1.11, the Goodness-of-Fitness Index (GFI) was 0.96, the Adjusted Goodness-of-Fitness Index (AGFI) was 0.94, and the Root Mean Square Residuals Index (SRMR) was 0.03. These findings provide valuable insights for formulating effective policies and concrete strategies to enhance and develop multicultural leadership among youth in diverse sociocultural contexts.